Remote Predictive Mapping 7. The Use of Topographic−Bathymetric Lidar to Enhance Geological Structural Mapping in Maritime Canada - Webster, Tim; MacGuigan, Kevin; Crowell, Nathan; Collins, Kate; MacDonald, Candace (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
An airborne topo-bathymetric lidar survey was conducted at Cape John, on the north shore of Nova Scotia, Canada, using the shallow water Leica AHAB Chiroptera II sensor. The survey revealed new bedrock features that were not discovered using previous mapping methods. A thick blanket of glacial till covers the bedrock on land, and outcrops are exposed only along the coastal cliffs and offshore reefs. The seamless landseabed digital elevation model produced from the lidar survey revealed significant bedrock outcrop offshore where ocean currents have removed the glacial till, a significant finding that was hitherto hidden under the sea surface. Several reefs were identified offshore as well as a major fold structure where block faulting occurs along the limbs of the fold. The extension of the Malagash Mine Fault located ~10 km west of Cape John is proposed to explain the local folding and faulting visible in the submerged outcrops. The extension of this fault is partially visible on land, where it is obscured by glacial till, and its presence is supported by the orientation of submerged bedding and lineaments on both the south and north sides of Cape John. This paper demonstrates how near-shore high-resolution topography from bathymetric lidar can be used to enhance and refine geological mapping.